Profil Belajar Mahasiswa S2 Pendidikan Bahasa Indonesia (Gaya Belajar, Aktivitas Belajar, Dan Kebiasaan Belajar) - Didi Yulistio (Mahesa Research Center, 2022)
Learning activities can be achieved by a learner or student if he pays attention to various internal factors, such as learning styles or types, learning activities, and study habits. The purpose of this study is to describe the learning profile of Indonesian Language Education Master's Degree students based on learning style factors, learning activities, and study habits. The scope of this research includes (1) learning style factors include visual, auditory, and kinesthetic types, (2) learning activity factors include visual, oral, auditory, motor, writing, and mental activities, and (3) study habits factors, includes regularity in learning includes planning, implementing processes, and completing tasks and remedial, discipline, using guidelines in learning, and concentration of mind in learning. This study uses a descriptive method and a simple quantitative approach. Data collection using a questionnaire technique includes factors of learning style, learning activities, and study habits. The research sample used the total affordability sampling technique, namely all 29 respondents of Masters in Indonesian Language Education FKIP Bengkulu University in the odd semester of 2018/2019. Data analysis was carried out quantitatively using the mean and percentage formula by describing the results qualitatively. Based on the results of the study, the study profiles of S2 Indonesian Language Education students, FKIP Bengkulu University, achieved an average score of 3.43 in the high category and the highest contribution was achieved starting from learning style factors (41.3%), learning activities (30.4%), and study habits. (by 28.3%). This means that the student learning profile has been carried out at the level of a good learning process. In particular, that this learning profile is achieved sequentially starting from the best achievement, namely factors (1) learning style with a tendency sequence starting from the auditory type, kinesthetic, and visual type, and (2) learning activities with a tendency sequence starting from the motor element. , writing, auditory, verbal, visual and mental, and (3) habits with tendencies sequentially starting from the elements of regularity, discipline, and concentration in learning.